Food Safety Training Through Nutrition Education and the Dangers of Plastic Packaging for Parents of Students at PKBM An-Nur Jakarta - Putri, Imawati Eka; Inaku, Awaluddin Hidayat Ramli; Ningtyas, Luthfiana Nurkusuma (EQUATOR SINAR AKADEMIA, 2025)
The indicators of food products quality are assessed by ingredients and packaging. This community partnership program activity aims to train parents of students at PKBM An-Nur East Jakarta to be able to read and understand the contents of food packaging labels such as nutritional information, production codes, expiration dates, halal logos, composition, and food packaging codes that are useful for parents of students in preparing their children's nutritional needs. This program began with the provision of a pre-test, education using lecture techniques to 50 participants (parents and teachers), filling out a post-test, and evaluating activities. There was an increase in the average post-test score (87) compared to the pre-test score (61). Lecture techniques and providing realistic examples effectively increased parents' understanding of food safety and reading nutrition labels at PKBM An-Nur Jakarta.